The unsung tale of the pied piper of haematology: insights from a case of renal transplant failure - Heera Shahir; Rohith Suresh; B.S. Vishnu; A Saifudeen (Clinical Medicine)
Background: Thrombotic events in young individuals require prompt identification of underlying prothrombotic conditions to prevent severe complications. Sticky platelet syndrome (SPS) is a thrombophilic disorder often underdiagnosed as a result of its non-specific presentation and lack of standardised testing. Case presentation: A 21-year-old man with no previous comorbidities presented with mild upper respiratory symptoms and was incidentally found to have elevated blood pressure, nephrotic range proteinuria and a markedly elevated serum creatinine level of 8 mg/dL. A renal biopsy confirmed IgA nephropathy, necessitating renal replacement therapy. Eight months later, he underwent a successful live-related donor renal transplant.On postoperative day 9, he developed decreased urine output, and Doppler imaging revealed transplant renal artery thrombosis. Haemodialysis sessions had to be resumed. Despite anticoagulation, recurrent thrombotic events ensued, including arteriovenous fistula thrombosis and graft venous thrombosis. Investigations and diagnosis: A detailed thrombophilia workup, including genetic sequencing for thrombophilia associated genes, was negative except for the platelet aggregation test. Platelet aggregation testing demonstrated increased response to low concentrations of ADP and epinephrine agonists, confirming the diagnosis of SPS (Table 1). Management: The patient was started on low-dose aspirin (75 mg daily) and apixaban (2.5 mg twice daily) while continuing maintenance haemodialysis. He remained free of further thrombotic events and was scheduled for a second renal transplant. Discussion: SPS is a thrombophilic disorder characterised by hyperactive platelet aggregation, leading to recurrent arterial and venous thrombotic events. It is implicated in 48% of all thromboembolic disorders, with unprovoked thrombosis occurring in 21% of arterial and 13% of venous cases.1 The exact mode of inheritance remains unclear, although genetic polymorphisms involving glycoprotein receptors and platelet activation pathways have been identified. Diagnosis relies on clinical suspicion and platelet function studies, given that genetic markers remain variable and complex.2Standard anticoagulation strategies may not fully mitigate thrombotic risk, but simple aspirin therapy has shown efficacy in reducing events.3 This case underscores the necessity of incorporating platelet aggregation tests in unexplained thrombosis to facilitate timely diagnosis and management. Conclusion: 1. SPS should be considered in patients with recurrent thrombosis, especially in the young and particularly in atypical circulatory sites. 2. Platelet aggregation testing is crucial in identifying SPS and guiding appropriate therapy. 3. Aspirin remains the mainstay treatment, preventing further thrombotic complications and improving patient outcomes.